THE ROLE OF BIOREPOSITORIES AND SPECIMEN MANAGEMENT IN SUPPORTING PRECISION MEDICINE RESEARCH AND CLINICAL TRIALS - Jamal Yahya Abuhaydar, Naif Khairallah Alhejaili, Ahmed Ali Moafa, Wedad Qubayl Alruwaytie, Ebtihal Lafi Alhejaili, Ibrahim Abdu Khairy, Amal Faisal Khalaf Alanazi, Ebtihal Abdullah Alotaibi, Meshari Fahad Almutairi,⁠ Ibrahim Abdu Khairy; Awadh Ghalib Anbari, Khaled Abdulrahman Mohammed Ali, Mousa Hammad Homid Alshammari, Alhanoof Ani Dhaher Alshamary, Amal Hameid Essa Alshammari, Riyadh Dhahawi Saleh Alharbi (Chelonian Research Foundation, 2022)
Biobanks play a crucial role in enhancing population health. We are now experiencing a new age in the field of medicine, when patients, health professionals, and researchers are increasingly working together to acquire fresh insights and investigate novel approaches to diagnose and cure diseases. Numerous extensive biobanking initiatives are now taking place globally, including institutions, nations, and even multinational collaborations. Biobanks are useful tools in translational research when combined with subject data from surveys and medical records. A biobank must possess samples of superior quality that satisfy the requirements of researchers. Biobank laboratory operations need extensive support, including lab and storage space, skills in information technology, a laboratory management information system, logistics for sample transfer, quality management systems, and suitable facilities. An essential measure of success for a biobank is the principle that each biospecimen deposited in the repository is associated with a participant who has valuable contributions to make towards research for a healthier future. This essay will examine the significance of biorepository activities, particularly in relation to the acquisition and preservation of participants' materials. Emphasis will be placed on preserving the quality of samples, as well as providing the necessary assistance to biorepositories in order to meet their objectives and maintain the integrity of each specimen. Keywords: Biobanks, biorepository activities, precision medicine research, review, laboratory research, specimen.